(untitled) (Ex Chordis, 2024)
Franco Margola (1908-1992) is still unanimously remembered as a talented composer and teacher. He uses a free musical language that links many elements: respect for tonality, the use of polytonality and a-tonalism, timid approaches to dodecaphony, and adherence to neoclassical instances. Margola’s music is «modern but not futuristic, cultured but not cerebral» (O. de Carli), and helps to fill a cultural void otherwise left by the modern avant-garde. It fully responds to the tastes of a public that wants to listen to the modern but does not want to abandon tradition or disown the past. The path here proposed would analyse Margola’s Violin production through the Sonata for Violin and Piano No. 1 dC 12. From a methodological point of view, it was necessary to directly analyse the score and different documentary sources: newspaper, reviews, essays, unpublished scores. The aim is to highlight the ways in which Margola gave an ancient form to new content, played an important role in updating the teaching of the Violin in Italian Conservatories of Music, and offered future musicians a possible way to understand the deep structure of music and the complex relationship between past and present.